Biological aspects of phage therapy versus antibiotics against Salmonella enterica serovar Typhimurium infection of chickens - Kosznik-Kwaśnicka, Katarzyna; Podlacha, Magdalena; Grabowski, Łukasz; Stasiłojć, Małgorzata; Nowak-Zaleska, Alicja; Ciemińska, Karolina; Cyske, Zuzanna; Dydecka, Aleksandra; Gaffke, Lidia; Mantej, Jagoda; Myślińska, Dorota; Necel, Agnieszka; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Phage therapy is a promising alternative treatment of bacterial infections in human and animals. Nevertheless, despite the appearance of many bacterial strains resistant to antibiotics, these drugs still remain important therapeutics used in human and veterinary medicine. Although experimental phage therapy of infections caused by Salmonella enterica was described previously by many groups, those studies focused solely on effects caused by bacteriophages. Here, we compared the use of phage therapy (employing a cocktail composed of two previously isolated and characterized bacteriophages, vB_SenM-2 and vB_Sen-TO17) and antibiotics (enrofloxacin and colistin) in chickens infected experimentally with S. enterica serovar Typhimurium. We found that the efficacies of both types of therapies (i.e. the use of antibiotics and phage cocktail) were high and very similar to one another when the treatment was applied shortly (one day) after the infection. Under these conditions, S. Typhimurium was quickly eliminated from the gastrointestinal tract (GIT), to the amount not detectable by the used methods. However, later treatment (2 or 4 days after detection of S. Typhimurium in chicken feces) with the phage cocktail was significantly less effective. Bacteriophages remained in the GIT for up to 2-3 weeks, and then were absent in feces and cloaca swabs. Interestingly, both phages could be found in various organs of chickens though with a relatively low abundance. No development of resistance of S. Typhimurium to phages or antibiotics was detected during the experiment. Importantly, although antibiotics significantly changed the GIT microbiome of chickens in a long-term manner, analogous changes caused by phages were transient, and the microbiome normalized a few weeks after the treatment. In conclusion, phage therapy against S. Typhimurium infection in chickens appeared as effective as antibiotic therapy (with either enrofloxacin or colistin), and less invasive than the use the antibiotics as fewer changes in the microbiome were observed.